Direito fundamental ao tempo razoável do processo judicial: limites e possibilidades de concretização no ordenamento jurídico pátrio - Nascimento, Carlos Francisco do (2010)
This dissertation aims to address the limits and possibilities of realizing the fundamental right to reasonable time of the Brazilian legal system process. From this perspective, we analyze a reasonable time concept for the process, consistent with the civil homeland process; the relationship between efficiency, effectiveness, legal security and reasonable time of adjudication; a formal recognition of the fundamental right to reasonable time of the procedure in the Constitution of 1988; and the immediate applicability of this fundamental right. As indicated, the crisis of the Judiciary and procedural delay are problems directly related to the limits and possibilities of realization of the fundamental right under study. Moreover, we also present some mechanisms that can be used to overcome these problems. The subject was developed based on constitutional interpretation of fundamental rights, an approach that will always have this concern to be based on a methodology which includes the normative and empirical-dogmatic fields, realizing the fundamental right to reasonable time of the process. We adopted as methodological approach the study of this issue in judicial aspect, more specifically in the field of civil procedure. Finally, we weave through a critical and analytical view, our conclusions, which demonstrate the possibilities of overcoming the limits imposed to immediate implementation of the fundamental right to reasonable time of the process in our legal system